2021
DOI: 10.3390/ijerph18168852
|View full text |Cite
|
Sign up to set email alerts
|

Heated Tobacco Products and Nicotine Pouches: A Survey of People with Experience of Smoking and/or Vaping in the UK

Abstract: Background: To gauge the public health impact of new nicotine products, information is needed on use among different populations. Aims were to assess in adults who smoked, vaped, did both or had recently stopped: (1) awareness, ever and current use of heated tobacco products (HTPs) and nicotine pouches (NP), (2) characteristics associated with ever use, (3) reasons for use of and satisfaction with HTPs, (4) characteristics associated with interest in use of HTPs. Methods: Online survey in the UK in 2019, n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 25 publications
(34 reference statements)
7
17
1
4
Order By: Relevance
“…Among US smokers, 5.6% had ever tried nicotine pouches in early 2021. Comparatively, a study conducted in late 2019 among UK current and former smokers and vapers found that 16% had ever heard of nicotine pouches and 4% had ever used them 14. Our study also found ever use of nicotine pouches significantly associated with age, education, previous quit attempts with traditional methods and ever SLT use.…”
Section: Discussionsupporting
confidence: 54%
“…Among US smokers, 5.6% had ever tried nicotine pouches in early 2021. Comparatively, a study conducted in late 2019 among UK current and former smokers and vapers found that 16% had ever heard of nicotine pouches and 4% had ever used them 14. Our study also found ever use of nicotine pouches significantly associated with age, education, previous quit attempts with traditional methods and ever SLT use.…”
Section: Discussionsupporting
confidence: 54%
“…Low product awareness is consistent with data from a 2019 online survey of UK adults who currently or formerly smoked or vaped. Only 15.9% of surveyed adults were aware of nicotine pouches, despite their current or former tobacco product use [ 22 ]. Moreover, a large majority of participants in this study (80.9%) would “definitely not” use nicotine pouches.…”
Section: Discussionmentioning
confidence: 99%
“…Among smokers who have used them, HTPs are generally not considered as sensory and psychologically satisfactory as cigarettes [28][29][30][31][32]. Rather, the most often-cited reasons to use were the belief that HTPs are "less harmful" or may support conventional cigarette smoking cessation [4,5,11,[33][34][35][36][37][38][39]. For those who continue using them, liking of the smell, taste, aftertaste, and ease of use are important predictors of continuation [40].…”
Section: Introductionmentioning
confidence: 99%
“…For those who continue using them, liking of the smell, taste, aftertaste, and ease of use are important predictors of continuation [40]. Perceived sensory benefits reported by users are less throat discomfort, better smell, appealing packaging, cleanliness, lack of ash and smoke, and availability of flavors [5,16,39]. Other reported reasons to use were lower costs, satisfaction and enjoyment, use in smoke-free places, new technology, and the product being more socially acceptable [5,11,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation